An Analysis of Factors Influencing Consumer Participation Interest to Improve Social Security Program Performance - Arianto, Chairul (Priviet Social Sciences Journal, 2024)
Seeing the development of the realization of achieving the target number of participants in BPJS Ketenagakerjaan since 2009 sd in 2013, almost every year do not reach the target. Achievement of the target number of active kepesertan ever achieved by BPJS Ketenagakerjaan 2012. BPJS Ketenagakerjaan need to create a marketing strategy that focuses on service marketing strategy, by improving strategy of People, Process, Physical Evidence. Formulation of the problem in this study is the extent of the influence strategies People, peroses and Physical Evidence of the performance through the consumer's interest to become participants in BPJS Ketenagakerjaan. The aim of this study was to determine and analyze the effect of strategies People, Process and Physical Evidence against BPJS Ketenagakerjaan performance through Minta consumers. The theory used is the marketing management of the marketing mix, especially in the theory of People, Process, Physical Evidence and consumer behavior. This research approach is supported by a case study with a survey. This type of research is deskreptif and quantitative research, the nature of research just to get a picture of a situation and problems and interpret. The population in this study were 12.5 million workers, with a sample size of 100 respondents. Data were collected through questionnaires and documentation study. Hypothesis testing using multiple linear regression analysis, F test and t test to determine the effect of independent variables on the dependent variable on kepesercayaan rate of 95% (α = 0.05). The results showed that the strategy of People, Process, Physical Evidence, partial direct effect only two independent variables, namely Process and Physical Evidence significant effect on interest. Domain is the most variable Physical Evidence (41%). Whereas to variable performance, partially only two independent variables, namely People and Interests significant effect on performance. The most dominant variable is a variable one (38.7%). Partially indirect influence most dominant variable that influence Physical Evidence of 9.84% on the performance memalui interest. The coefficient of determination (R ²) showed independent variables studied were able to explain 36.6% tehadap variables remaining 63.4 secangkan performance is explained by the other independent variables that are not included in this study.